Determinan Faktor Minat Investasi Pada Platform Peer To Peer Lending Syariah: Studi pada Kab. Bone - Aura Lila Dwini; Andi Patimbangi; Muhammad Ardi (Faculty of Islamic Economics and Business, 2026)
This study aims to analyze the influence of service convenience and platform trust on public investment interest in Sharia Peer-to-Peer (P2P) Lending in Bone Regency. This research employed a quantitative approach using multiple linear regression analysis. Data were collected through questionnaires distributed to 50 Muslim respondents domiciled in Bone Regency who had knowledge of or exposure to Sharia P2P Lending services. The results show that platform trust has a positive and significant effect on investment interest, with a regression coefficient of 0.645 and a significance value of 0.040. Meanwhile, service convenience has a positive but insignificant effect, with a regression coefficient of 0.309 and a significance value of 0.294. Simultaneously, service convenience and platform trust significantly influence public investment interest, as indicated by an F value of 21.220 and a significance value of 0.000. These findings indicate that trust in platform security, transparency, and Sharia compliance is more decisive than technical convenience in encouraging public investment interest in Sharia P2P Lending. This study contributes to Islamic fintech literature by integrating the Technology Acceptance Model, particularly perceived ease of use, with platform trust in the context of regional Sharia digital investment behavior.